Control of algal growth in reservoirs with ultrasound - Purcell, Diane (Cranfield University, 2009)
Algal blooms are a major worldwide water treatment concern due to their potentially harmful effects on humans and livestock. The main cause of algal bloom proliferation is eutrophication of water sources. Anthropogenic effects contribute significantly to the increased levels of nutrients within source waters. With the world‘s population continuing to grow the likelihood is that algal blooms will worsen in the future. Algal blooms can cause release of toxins which in high concentrations are a serious health hazard for humans and animals. Blooms ability to grow rapidly consuming nutrients and oxygen, at such an elevated rate that anoxia can occur increasing the incidences of fish kills and rates of bacterial growth, consequently recreational use of water sources may be suspended. From a water treatment perspective algal cells can block filters for example diatoms, green species increase turbidity and chlorophyll a, and cyanobacteria produce taste and odour issues related usually to toxin release among other problems increasing the chemical demand necessary to treat the water supply. Algal bloom control measures that are presently employed range from nutrient limitation to aeration and destratification. Phosphorus and nitrogen are the two main nutrients which enhance bloom growth, so if prevention of nutrient accumulation could be implemented this would be considered the best solution for bloom prevention, yet this has proved to be difficult. To find bloom control methods which are green that is to consume little energy, reduce water treatment costs and chemical use in water treatment, is a challenge. However recent investigations into the use of ultrasound have confirmed it as being one such method. Successful use of ultrasound in numerous other applications including wastewater treatment made it an ideal candidate to test as a green solution to algal bloom control. Cont/d.